A trial of pharmacy‐based testing for Chlamydia trachomatis using postal specimen kits. (23rd December 2016) - Debattista, Joseph; Hayes, Meghan; Marshall, Penelope; Pouchkareff, Nickolas; Gordon, Rose; Priddle, Alannah
Abstract: Background: Chlamydia trachomatis infection is the most commonly notified sexually transmissible bacterial infection in the developed world. An effective approach to improve screening lies with programs that specifically target high risk populations through accessible testing strategies. Objective: To pilot the distribution of chlamydia postal testing kits through a network of community pharmacies. Methods: Chlamydia postal test kits, adapted from a current online service, were sold at a minimal price across 18 community pharmacies located in Brisbane. Samples, collected by Uri swab, were mailed to a centralised service for processing, and results directly communicated to clients. Results: Over a 9‐month period, 333 test kits were made available through pharmacies, of which 109 (32.7% of total) were sold. Of these, 43 specimens were returned for processing, comprising 39.4% of sales, or 12.9% of total. Of these returned samples, seven (16.3% of specimens) returned a reactive result, 34 specimens were non‐reactive and one was invalid. Conclusions: Despite a low specimen return rate (12.9% of total kits available, 39.4% of kits sold), a high reactivity rate (16.3%) for chlamydia was identified among those persons purchasing a kit and returning a sample, suggesting that the pharmacy program had been effectively targeted. Overall, this pilot has demonstrated the feasibility of a system for distributing chlamydia test kits through pharmacy and the use of the existing health infrastructure to follow up results and manage clients.